A Case of Isolated Thyroid Stimilating Hormone Deficiency - Cho, Hyun Wook; Kim, Yeo Joo; Kim, Sang Jin (Soonchunhyang medical science, 2012)
Isolated thyroid stimulating hormone (TSH) deficiency is very rare. Only a few patients are reported in the world. A 50-year-old woman was admitted to Soonchunhyang University Cheonan Hospital because of a distal radius fracture. She was diagnosed with hypothyroidism incidentally. Serum free T4 and TSH were low. After administration of exogenous TSH releasing hormone, no TSH response was noted. The response of prolactin and other pituitary hormones were appropriate after stimulation. Pituitary magnetic resonance image did not reveal any abnormalities. The diagnosis of isolated TSH deficiency was established for this patient. KCI Citation Count: 0